PENGARUH CAR, LDR, NPL, TINGKAT INFLASI, DAN KEBIJAKAN PERUBAHAN ATURAN DEFINISI UMKM TERHADAP SHARE PENYALURAN KREDIT UMKM OLEH PERBANKAN DI INDONESIA - Tika, Regina Mutiara (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The aim of this study was to analyze the effect of banking internal factors such as CAR, LDR, and NPL , and also external factors such as inflation rate and policy about the change of SMEs definition on share of SMEs credit in banking sector in Indonesia. This study using descriptive analysis. The result of this study are even CAR, LDR, and NPL have positive and negative effect on share of SMEs credit in banking sector in Indonesia. Meanwhile, inflation rate not only has negative effect on share of SMEs credit in banking sector in Indonesia but sometimes it has no effect on share of SMEs credit. Policy about the change of SMEs definition in Indonesia has negative effect on share of SMEs credit in banking sector in Indonesia. Keywords : Share of SMEs creditÂ , CAR, LDR, NPL, Inflation rate, Policy about the change ofÂ SMEs definiton.